Personality, study habits and preferences for television genres in university students - Montgomery Urday, William (2003)
It's very important to get facts of interaction between intellective and emotional aspects of young audience in connection with TV effects. In this work it's applied three tests for measurement of personality factors, study habits and televisive habits consume in 264 subjects, with the goal to know and to analyze your general profiles and relationships. The results to showed some mean differences in men and women on several topics, and some mean relations between personality factors, study strategies and televisive consume.